Cervical Vestibular-Evoked Myogenic Potentials and Balance Testing in Children with Down Syndrome - Kaya,Sule (2021)
Abstract Introduction Vestibular otolith function plays a major role in balance control. Objective To investigate the saccular and balance functions of children with Down syndrome (DS). Methods In total, 15 children with DS aged between 9 and 11 years were included. An age- and gender-matched control group (CG) composed of 15 normal participants was also included. The subjects with DS had trisomy 21, without hearing or organic problems, and they had independence in stance. The saccular function among the children with DS and among the controls was tested using air-conduction cervical vestibular-evoked myogenic potentials (cVEMPs). In addition, the static and dynamic balance statuses were evaluated using the following assessments; the Pediatric Balance Scale (PBS), the modified Clinical Test of Sensory Interaction on Balance (mCTSIB), the Romberg test, and the Timed Up and Go (TUG) test. Results In the present study, the results of the saccular function test showed that there was a significant difference between children with and without DS (p < 0.05). The DS subjects had significantly earlier N1 latancy and lower amplitude of the cVEMPs (< 70 μV) compared with the control subjects. The static-dynamic balance ability was statistically and significantly different in children with DS compared with the controls (p < 0.05). Conclusion These results revealed that saccular function seems to be affected in DS subjects. The dysfunction in static and dynamic balance abilities of the children with DS may be attributed to vestibular dysfunction as well as low gross motor skills. This knowledge should be taken into account when assessing motor performance in those subjects. Additional larger studies testing other dimensions of the vestibular system in children with DS are needed.